The sociological dimension of external military interventions: the Portuguese military abroad - Carreiras, H. (2015)
This article addresses, from a sociological point of view, the involvement of the Portuguese armed forces in international peace operations. After reviewing some major sociological contributions for understanding change in military institutions and the development of international military missions, it concentrates on the Portuguese case, aiming at uncovering the place and meaning of peace operations for the Portuguese armed forces during the past two decades. After briefly recalling some facts and figures concerning the Portuguese participation in peace operations, it addresses the relevance of such involvement at different analytical levels, show- ing that peace operations have come to play a decisive role in the national defence political discourse, the organizational configuration of the Portuguese armed forces and the soldiers’ professional identity. The last section consists of a short prospective exercise looking at possible implications of disengagement from international peace missions. The conclusion is that, considering the strategic, organizational and socio- psychological centrality of these missions, disengagement is likely to have impor- tant consequences in the overall strategic definition, purpose and identity of the Portuguese military, while entailing an additional cost: the possible loss of at least part of a recently reinforced legitimacy.